Financial management and policy - Van Horne, James C. (Upper Saddle River, N.J. : Prentice Hall, 1986)
Highly respected for its effective integration of financial theory and practice, this classic text explores the rapidly evolving and exciting theory of finance as it relates to a corporation's investment in assets, financing, and dividends, explains the ways in which analytical techniques are brought to bear on financial decision making, and supplies the institutional material necessary for a solid understanding of the environment in which financial decisions are made.
Includes bibliographical references and index.
uaa 25/01/19
Loans
Keywords: Corporations; Financial management; Financial policy